Prevalence and correlates of diabetes and impaired fasting glucose among adults in Afghanistan: Insights from a national survey - Omid Dadras; Anita Nyaboke Ongosi; Chia-Wen Wang (SAGE Open Medicine, 2024)
Objectives: Afghanistan is experiencing an escalating burden of noncommunicable diseases, with diabetes and impaired fasting glucose being of particular concern. To explore the prevalence of diabetes and impaired fasting glucose and associated factors among adult Afghans. Methods: This cross-sectional study used secondary data from a nationally representative survey, conducted in 2018 in Afghanistan. A blood sample was collected from the fingertip and tested through a strip to measure blood glucose. The complex sampling design and sampling weights were accounted for in all analyses to produce representative estimates of the target population in Afghanistan. Results: Of 3890 Afghan adults aged 18–69 years who participated in this survey, 11.07% and 10.32% had diabetes and impaired fasting glucose, respectively. For overweight individuals with abdominal obesity, the risk for diabetes became significantly elevated, with an adjusted relative risk ratio of 2.12 (95% CI: 1.10–4.09). However, the most pronounced effect was observed among individuals classified as having obesity with abdominal obesity with an adjusted relative risk ratio of 2.54 (95% CI: 1.37–4.70). Moreover, high cholesterol level was significantly associated with both impaired fasting glucose (ARRR: 2.52, 95% CI: 1.55–4.12) and diabetes (ARRR: 4.12, 95% CI: 2.59–6.56), whereas high blood pressure was significantly associated with only diabetes (ARRR: 1.82, 95% CI: 1.16–2.86). Conclusions: This investigation provides critical insight into the prevalence of diabetes and IFG among Afghan adults aged 18–69 years. Relative to the global average, the higher prevalence observed calls for specifically designed interventions targeting individuals with cardiometabolic risk factors, such as elevated body mass index, abdominal obesity, hypertension, and hypercholesterolemia.